2015
DOI: 10.1097/nur.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Building a Unit-Level Mentored Program to Sustain a Culture of Inquiry for Evidence-Based Practice

Abstract: Despite typically high turnover rates of military personnel and restructuring of 3 facilities during the study period, the readiness for, beliefs about, and implementation of EBP improved. This study suggests that a commitment to an EBP culture may diffuse among individuals in an organization, even while experiencing significant change. It also demonstrates that a unit-level mentored EBP program is sustainable despite changes in organizational structure and workforce composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
(58 reference statements)
1
30
0
Order By: Relevance
“…The second use of this assessment used the same questions in a primary care setting related to eHealth tool deployment, in addition to a supplemental questionnaire [24]. Finally, the Evidence-Based Practices Beliefs scale was used in three hospitalbased settings, the first time when it was being developed [25] and later in two samples of hospital-based nurses as part of a battery of assessments [26,27]. The 18 individually developed assessments were fielded in a variety of settings, including many types of clinical settings: primary care, long-term care, hospitals, rehabilitation, and mental health.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The second use of this assessment used the same questions in a primary care setting related to eHealth tool deployment, in addition to a supplemental questionnaire [24]. Finally, the Evidence-Based Practices Beliefs scale was used in three hospitalbased settings, the first time when it was being developed [25] and later in two samples of hospital-based nurses as part of a battery of assessments [26,27]. The 18 individually developed assessments were fielded in a variety of settings, including many types of clinical settings: primary care, long-term care, hospitals, rehabilitation, and mental health.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Eleven uses employed the specific phrase "Organizational Readiness for/to Change" [8, 10, 17, 21-24, 35, 41, 43], with an additional eight uses of "Organizational Readiness for [a specific intervention]" (e.g. e-Health) [11,26,27,32,38,39,42]. Other variations included "Practice Capacity for Change," [31] "Preparedness for Change," [34] and "Readiness to Engage in EBP."…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Nurses who participate in EBP programmes feel empowered to question and improve practice (Christenbery et al., 2016). The Institute of Medicine’s 2020 goal that 90% of all care decisions are evidence-based has encouraged healthcare institutions to foster a culture of EBP through educational initiatives designed to promote nurses’ EBP knowledge and skill (Breckenridge-Sproat et al., 2015; Christenbery et al., 2016; Melnyk et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Advancing Research and Clinical practice through close Collaboration model, EBP mentors are essential to building and sustaining a culture of EBP by supporting nurses and clinicians at the point-of-care (Breckenridge-Sproat et al., 2015; Melnyk, 2012). Due to the essential role of mentors, educational initiatives have focused on utilising mentorship as part of a multifaceted approach to conducting EBP scholarship (Chan et al., 2020; Spiva et al., 2017; Wallen et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed a high level of variation in the length and composition of EBP mentor training programs (see Table S2). Interventions varied in length from fewer than three months to one year, with the majority lasting six months to one year (Abdullah et al, 2014;Breckenridge-Sproat et al, 2015;Chan, Glass, & Phang, 2020;Cullen et al, 2020;Kim et al, 2017;Melnyk et al, 2017;Royer, Crary, Fayram, & Heidrich, 2018). The most prevalent interventions included didactic content, an EBP project with individual or group coaching sessions, and an EBP toolkit or printed resources to supplement training.…”
Section: Interventionsmentioning
confidence: 99%